Ho Chi Minh's Ideology on National Unity in Vietnam's Revolution - Tran Thi Dieu (Center for Southeast Asian Social Studies (CESASS), 2020)
For any country in the stage of development, unity is always considered as palpable pilar for a stable and sustainable goal of welfare. This study focuses on the case of Vietnam by analysing Ho Chi Minh’s ideology. He is the initiator and builder of Vietnamese nation known as the ideology on great unity which continues to be expressed from theory to practice. Great national unity is both the goal and the top task of the revolution which may be seen thoroughly in all paths, guidelines and policies of the Party during the Party Congresses. This article further discusses the basis for the formulation of the national unity based on Ho Chi Minh’s ideology, explain why Ho Chi Minh can solve the national-class relationship, and draw out the implication for Vietnam in the stage of current development.